Human mobility data in the COVID-19 pandemic: characteristics, applications, and challenges. Issue 9 (2nd September 2021) - Hu, Tao; Wang, Siqin; She, Bing; Zhang, Mengxi; Huang, Xiao; Cui, Yunhe; Khuri, Jacob; Hu, Yaxin; Fu, Xiaokang; Wang, Xiaoyue; Wang, Peixiao; Zhu, Xinyan; et al.
ABSTRACT: The COVID-19 pandemic poses unprecedented challenges around the world. Many studies have applied mobility data to explore spatiotemporal trends over time, investigate associations with other variables, and predict or simulate the spread of COVID-19. Our objective was to provide a comprehensive overview of human mobility open data to guide researchers and policymakers in conducting data-driven evaluations and decision-making for the COVID-19 pandemic and other infectious disease outbreaks. We summarized the mobility data usage in COVID-19 studies by reviewing recent publications on COVID-19 and human mobility from a data-oriented perspective. We identified three major sources of mobility data: public transit systems, mobile operators, and mobile phone applications. Four approaches have been commonly used to estimate human mobility: public transit-based flow, social activity patterns, index-based mobility data, and social media-derived mobility data. We compared mobility datasets' characteristics by assessing data privacy, quality, space–time coverage, high-performance data storage and processing, and accessibility. We also present challenges and future directions of using mobility data. This review makes a pivotal contribution to understanding the use of and access to human mobility data in the COVID-19 pandemic and future disease outbreaks.